Extrasynaptic Neurotransmission Mediated by Exocytosis and Diffusive Release of Transmitter Substances - Del-Bel, Elaine; De-Miguel, Francisco F. (Frontiers in Synaptic Neuroscience, 2018)
This review deals with the mechanisms of extrasynaptic release of transmitter substances, namely the release from the soma, axon and dendrites in the absence of postsynaptic counterparts. Extrasynaptic release occurs by exocytosis or diffusion. Spillover from the synaptic cleft also contributes to extrasynaptic neurotransmission. Here we first describe two well-known examples of exocytosis from the neuronal soma, which may release copious amounts of transmitter for up to hundreds of seconds after electrical stimulation. The mechanisms for somatic exocytosis of the low molecular weight transmitter serotonin, and the peptides oxytocin and vasopressin have been studied in detail. Serotonin release from leech neurons and oxytocin and vasopressin from rodent neurons have a common multi-step mechanism, which is completely different from that for exocytosis from presynaptic endings. Most transmitters and peptides released extrasynaptically seem to follow this same mechanism. Extrasynaptic exocytosis may occur onto glial cells, which act as intermediaries for long-term and long-distance transmission. The second part of this review focuses on the release upon synthesis of the representative diffusible molecules nitric oxide (NO) and endocannabinoids. Diffusible molecules are synthesized "on demand" from postsynaptic terminals in response to electrical activity and intracellular calcium elevations. Their effects include the retrograde modulation of presynaptic electrical activity and transmitter release. Extrasynaptic neurotransmission is well exemplified in the retina. Light-evoked extrasynaptic communication sets the gain for visual responses and integrates the activity of neurons, glia and blood vessels. Understanding how extrasynaptic communication changes the function of hard-wired circuits has become fundamental to understand the function of the nervous system.